2018
DOI: 10.1007/s00592-018-1117-z
|View full text |Cite
|
Sign up to set email alerts
|

Progression of diabetic retinopathy severity after treatment with dexamethasone implant: a 24-month cohort study the ‘DR-Pro-DEX Study’

Abstract: This study provides the first long-term evidence that DEX implant has the potential to not only delay progression of DR and PDR development, but may also improve DR severity over 24 months. Better understanding of the effects of corticosteroids will help guide its use in the treatment pathway of DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 39 publications
0
54
0
1
Order By: Relevance
“…Moreover, some patients have poor response to the drugs after a long-term treatment [11]. Apart from anti-VEGF drugs, some other therapies have also impacted macular disease treatment and showed their effectiveness, such as dexamethasone implant [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some patients have poor response to the drugs after a long-term treatment [11]. Apart from anti-VEGF drugs, some other therapies have also impacted macular disease treatment and showed their effectiveness, such as dexamethasone implant [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…110 Similar data obtained from the DR-Pro-DEX Study and others demonstrated that the dexamethasone and fluocinolone implants significantly delayed the progression and reduced the severity of DR over a 24-month study period. 153,154 Nonsteroidal Anti-Inflammatory Drugs Nonsteroidal anti-inflammatory drugs (NSAIDs) for DME have not been studied in depth, but available investigations suggest that they have little role in its management. Protocol R of the DRCR Network was a prospective, masked, randomized clinical trial of topical nepafenac 0.1% three times per day versus placebo over 12 months in eyes with noncenter-involved DME and good VA. 155 No differences in VA outcomes were found.…”
Section: Corticosteroid Therapymentioning
confidence: 99%
“…Corticosteroids reduce not only leukostasis and inflammatory cytokine production, but also VEGF expression [19]. Several studies have indicated that steroids were effective and safe for diabetic macular edema (DME) eyes' treatment [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%